PENGARUH UKURAN PERUSAHAAN, KOMISARIS INDEPENDEN, KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL TERHADAP INTEGRITAS LAPORAN KEUANGAN(STUDI EMPIRIS PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017) - Armel, Raja Jaka Perdana; Desmiyawati, Desmiyawati; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aimed to determine the influence of company size, independentdirectors, audit committee and institutional ownership on the integrity of thefinancial statement. Independent variables used in this study are company size,independent directors, audit committee and institutional ownership, while thedependent variable in this study is the integrity of the financial statement.Populations used in this study is LQ 45 companies listed on IDX 2015-2017 wherethe total population is used by 45 companies. The sampling technique used waspurposive sampling technique in which the number of observations obtained thisstudy was 135 (45x3). Data analysis conducted with multiple regression with helpof software SPSS version 20,0. Of the result of the testing that has been done,showed that the independent variables Company Size which has a significantinfluence on integrity of financial statement, Independent Directors which has asignificant influence on integrity of financial statement, Audit Committee whichhas a significant influence on integrity of financial statement, InstitutionalOwnership which has a significant influence on integrity of financial statement.Keywords : Company Size, Independen Directors, Audit Committee, InstitutionalOwnership, Integrity of the Financial Report.